2013
DOI: 10.1038/srep03063
|View full text |Cite
|
Sign up to set email alerts
|

Controllable emission of a dipolar source coupled with a magneto-dielectric resonant subwavelength scatterer

Abstract: We demonstrate experimentally and theoretically that a local excitation of a single scatterer of relative dielectric permittivity ε = 6 permits to excite broad dipolar and quadrupolar electric and magnetic resonances that shape the emission pattern in an unprecedented way. By suitably positioning the feed with respect to the sphere at a λ/3 distance, this compact antenna is able to spectrally sort the electromagnetic emission either in the forward or in the backward direction, together with a high gain in dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 35 publications
2
51
0
Order By: Relevance
“…These modes can be easily and efficiently excited either from near or far field illumination [1][2][3]. This novel class of photonic resonators is very promising to design directive antennas [4][5][6], to enhance the electric or magnetic near field intensities [7][8][9][10], to design subwavelength sized light cavities [8,11,12], to host frequency mixing processes such as third harmonic generation [13], and even to create isotropically polarized speckle patterns [14].…”
Section: Introductionmentioning
confidence: 99%
“…These modes can be easily and efficiently excited either from near or far field illumination [1][2][3]. This novel class of photonic resonators is very promising to design directive antennas [4][5][6], to enhance the electric or magnetic near field intensities [7][8][9][10], to design subwavelength sized light cavities [8,11,12], to host frequency mixing processes such as third harmonic generation [13], and even to create isotropically polarized speckle patterns [14].…”
Section: Introductionmentioning
confidence: 99%
“…Various nanoantennas have been investigated that exhibit such higher order multipole moments to achieve a directional response [12,[25][26][27]. We study the application of the generalized Kerker condition to a plasmonic nanoring antenna.…”
mentioning
confidence: 99%
“…It is recently shown that through overlapping electric and magnetic multipoles of higher orders, ultra-directional forward scattering pattern could be obtained [23,40,41]. Those demonstrations either rely on specific incident dipole sources [40,41] or on composite core-shell structures [23], where the condition of super-scattering cannot always be guaranteed.…”
Section: Ultra-directional Super-scattering Of Radially Anisotropic Pmentioning
confidence: 99%